Multilayer stress field interference in sandstone and mudstone thin interbed reservoir. (9th September 2016) - Guo, Jian-Chun; Luo, Bo; Zhu, Hai-Yan; Yuan, Shu-Hang; Deng, Yan; Duan, You-Jing; Duan, Wei-Gang; Chen, Li
Abstract: General fracturing and separate layer fracturing play an important role in sandstone and mudstone thin interbed (SMTI) reservoirs, where one of the main issues is to control the excessive height growth of fracturing. The fracture propagation at the interface depends on the induced stress produced by the hydraulic fracturing construction. This paper employed a poroelastic coupled damage element with the cohesive zone method (CZM) to establish a 2D fracture quasi-static propagation model. A parametric study was performed under different fracture height, fracture width, pumping rate, fluid viscosity, in situ stress, elastic modulus and tensile strength with this model. General fracturing and separate layer fracturing are compared with each other through fracture morphology and induced stress. The simulation results show that the absolute value of induced stress increases with the decrease in matrix stress near the fracture tip. As a result, the propagation of the fractures is much easier due to the weakened degree of compression. The growth of fracture height and width, the increase in pumping rate and the excessively large or small value of fluid viscosity lead to larger induced stress on the interface. Higher in situ stress, lower elastic modulus, and higher tensile strength of the interlayers can control the excessive height growth of fracturing. The simulated results also show that the fractures are more likely to be overlapped with each other in general fracturing compared to that in separate-layer fracturing. Results of the simulations suggest that lower pumping rates, the proper value of fluid viscosity, separate layer fracturing and interlayers with higher in situ stress, lower elastic modulus and higher tensile strength tend to limit fracture height. Finally, the proposed model was applied to a practical oil field case to verify its effectiveness.